LIVING THE QUR'AN AMID FLEXING CULTURE: STRENGTHENING RELIGIOUS AND SOCIAL VALUES IN MADURAN SOCIETY - Taufiqur rahman; Ahmad Zaini; Saidatul Karimah (Mozaic: Islamic Studies Journal, 2023)
Living Qur’an in the context of flexing culture becomes an intriguing phenomenon when religious practice intersects with a lifestyle of displaying wealth and social status. In Madurese society, this condition presents both tensions and opportunities between strong religious traditions and the currents of modern popular culture. This study aims to examine how the practice of Living Qur’an functions as a reinforcement of religious values amid the widespread culture of flexing in Madurese society. In addition, this study seeks to analyze the role of Qur’anic values in shaping social awareness that is critical of consumptive behavior and excessive pursuit of social recognition. The research method employed is qualitative with a case study approach through observation, interviews, and analysis of religious documents as well as the social practices of the community. The findings indicate that Living Qur’an can serve as a foundation for the internalization of the values of simplicity, gratitude, and social concern, which counterbalance the impulse to flex in everyday life. The practices of reciting, studying, and implementing the Qur’an within pesantren environments and Madurese families act as a moral bulwark that guides more proportional patterns of consumption and social interaction. Nevertheless, flexing culture facilitated by social media continues to exert a significant influence, especially on the younger generation, resulting in a tension between religious values and the desire for visibility in digital public spaces. This study also identifies a gap in previous research, which has rarely linked Living Qur’an studies with the phenomenon of flexing in a specific manner within the context of Madurese society, thereby offering a new contribution to the enrichment of Qur’anic and contemporary cultural studies.